Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Profitabilitas, Ukuran Perusahaan Terhadap Kebijakan Deviden Sektor Industri Barang Konsumsi Di Bursa Efek Indonesia (Periode Tahun 2017-2019) - Kholilah Zuhairoh; Ronny Malavia Mardani; Nurhidayah Nurhidayah (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Determine the effect of managerial ownership on Dividend Payout Ratio in the consumer goods industry sector. Knowing the effect of institutional ownership on dividend Payout Ratio. Knowing the effect of profitability on dividend policy in consumer goods industrial sector companies. Knowing the effect of company size on dividend Payout Ratio in companies in the consumer goods industry sector. The method used in this research is explanatory research in order to find the effect of the independent variables on the dependent variable. The results obtained in this study are managerial ownership, profitability and firm size which have a negative effect on dividend policy while institutional ownership has a positive effect on dividend Payout Ratio. Keywords: Managerial Ownership, Institutional Ownership, Profitability, Company Size, and Dividend Payout Ratio